Whey protein supplement adulteration with rice flour quantification: A simple method using ATR-FT-MIR and iPLS - Braga, Soraia C. G. N. (2021)
In this work, a method using ATR-FT-MIR and iPLS was developed to quantify whey protein supplement adulteration with rice flour. The original vanilla flavor commercial whey protein samples were adulterated with commercial rice flour with concentrations between 11.49% to 29.14% (w/w). After the adulteration, the ATR-FT-MIR spectra were obtained with no additional preparation procedure. The iPLS model analysis was performed using RStudio software with the mdatools package. The RMSEC was 1.26, the R2= 0.954 and the cross-validation error (RMSECV) was 3.31. The prediction error (RMSEP) for the validation set was equal 3.48 and the validation R2 was 0.610. These parameters, associated with the fact that the method does not require sample preparation, demonstrate the procedure viability as a tool to quantify adulterations of whey protein with rice flour.